Effect of Exogenous Bacillus sp. Addition on Bioremediation of Soil Contaminated by Used Cooking Oil - Fauziah, Aisyah Fikria; Prameswari, Alfi Hanifah; Polandos, Chersy Tiffany; Kocha, Santana; Yuliandini, Sinta; Surakusumah, Wahyu; Dewina, Restu Utari (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2024)
Used cooking oil waste can be carcinogenic and toxic to living creatures in soil. Bioremediation is a way to treat used cooking oil-contaminated soil by using microorganisms that are safe for the environment. This research aimed to determine the effect of adding exogenous bacteria Bacillus sp. on the bioremediation process of soil contaminated with used cooking oil waste. Total Petroleum Hydrocarbons (TPH) measurement and effectiveness of Bacillus sp. in degrading hydrocarbons was calculated in this study. The results showed that Bacillus sp. has the ability to rapidly degrade used cooking oil TPH and increased the effectiveness of bioremediation in soil.